The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/biomedicines11102702
|View full text |Cite
|
Sign up to set email alerts
|

Legend or Truth: Mature CD4+CD8+ Double-Positive T Cells in the Periphery in Health and Disease

Magdalena Hagen,
Luca Pangrazzi,
Lourdes Rocamora-Reverte
et al.

Abstract: The expression of CD4 and CD8 co-receptors defines two distinct T cell populations with specialized functions. While CD4+ T cells support and modulate immune responses through different T-helper (Th) and regulatory subtypes, CD8+ T cells eliminate cells that might threaten the organism, for example, virus-infected or tumor cells. However, a paradoxical population of CD4+CD8+ double-positive (DP) T cells challenging this paradigm has been found in the peripheral blood. This subset has been observed in healthy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(157 reference statements)
1
1
0
Order By: Relevance
“…For example, we found relatively high BACH2 levels in DN T cells but low BACH2 levels in DP T cells compared to other normal peripheral T-cell subsets. This finding seems to be in concordance with the physiological roles of BACH2 [ 12 , 13 ], since peripheral DN T cells are essential for maintaining immune homeostasis under healthy conditions and contribute to immune surveillance and defense [ 33 35 ], whereas DP T cells in the periphery exhibit memory-like features [ 36 , 37 ]. As such, further efforts are needed to delineate the molecular mechanisms that govern BACH2 transcription or post-transcriptional regulation in normal and malignant T cells, thus elucidating the biological function of BACH2 in scenarios of both health and disease.…”
Section: Discussionsupporting
confidence: 67%
“…For example, we found relatively high BACH2 levels in DN T cells but low BACH2 levels in DP T cells compared to other normal peripheral T-cell subsets. This finding seems to be in concordance with the physiological roles of BACH2 [ 12 , 13 ], since peripheral DN T cells are essential for maintaining immune homeostasis under healthy conditions and contribute to immune surveillance and defense [ 33 35 ], whereas DP T cells in the periphery exhibit memory-like features [ 36 , 37 ]. As such, further efforts are needed to delineate the molecular mechanisms that govern BACH2 transcription or post-transcriptional regulation in normal and malignant T cells, thus elucidating the biological function of BACH2 in scenarios of both health and disease.…”
Section: Discussionsupporting
confidence: 67%
“…The gut immune system plays a key role in this perturbation of homeostasis between commensal bacteria and the function of the gut barrier [ 6 ]. Its response involves the activation of a variety of intestinal immune cells, including neutrophils, macrophages, T cells, B cells, and dendritic cells [ 7 , 8 ]. It has been observed that the pro-inflammatory CD8 + cytotoxic T lymphocytes can induce a relapse of colitis via the production of interferon-γ in mice [ 9 ].…”
Section: Introductionmentioning
confidence: 99%